AB0650 Survival and Organ Involvement in Patients with Limited Cutaneous Systemic Sclerosis and Anti-Topoisomerase Antibodies. (15th July 2016) - Kranenburg, P.; Van Den Hombergh, W.M.T.; Knaapen-Hans, H.K.; van den Hoogen, F.H.; Fransen, J.; Vonk, M.C.
Abstract : Background: In systemic sclerosis (SSc) there are two main subgroups based on skin involvement: limited cutaneous systemic sclerosis (lcSSc) and diffuse cutaneous systemic sclerosis (dcSSc). LcSSc is associated with the presence of anti-centromere antibodies (ACA) and a more subtle disease course, whereas dcSSc is associated with anti-topoisomerase antibodies (ATA) and often a more severe disease course. Nevertheless, despite the associations between clinical subtype and autoantibodies, there are quite a number of SSc patients who have limited skin involvement and antibodies associated to diffuse skin involvement (ATA). The question is whether these patients have a disease more like lcSSc or more like dcSSc. Objectives: The aim of this study is to determine whether survival and organ involvement in lcSSc patients who are ATA positive are similar to lcSSc ATA negative patients or to dcSSc ATA positive patients. Furthermore, the relation between ATA positivity and time to transition from lcSSc to dcSSc was evaluated. Methods: Data from The Nijmegen Systemic Sclerosis cohort were used. Survival analysis was performed to show cumulative survival and time to event for Interstitial Lung Disease (ILD), Pulmonary Arterial Hypertension (PAH), cardiac involvement, Scleroderma Renal Crisis (SRC), and transition to lcSSc. Cox proportional hazard modelling was performed to adjust for confounders. Results: Survival up to 15 years of follow-up was highest in lcSSc ATA positive patients, whereas dcSSc ATA positive patients had lowest survival (table 1 ). Interstitial Lung Disease (ILD) occurred more frequently in lcSSc ATA positive patients compared to lcSSc ATA negative patients. However, a higher frequency of ILD was seen dcSSc ATA positive patients. No significant differences were seen between the four (table 1 ) subgroups in occurrence of PAH, cardiac involvement and SRC. At the moment of diagnosis, 343 patients were classified as lcSSc and 48 of these patients evolved from lcSSc to dcSSc, 24 (9%) in the ATA negative subgroup and 24 (29%) in the ATA positive subgroup (figure 1 ). Conclusions: This study showed that lcSSc ATA positive patients differ from lcSSc ATA negative patients and dcSSc ATA positive patients concerning both survival and occurrence of ILD. Therefore, in everyday clinical practice, the prognosis of lcSSc ATA positive patients should be considered separately. Disclosure of Interest: None declared